2021
DOI: 10.1007/s11665-021-06186-1
|View full text |Cite
|
Sign up to set email alerts
|

Design, Manufacturing, and Characterization of Hybrid Carbon/Hemp Sandwich Panels

Abstract: Advanced sandwich composite structures that incorporate foams or honeycombs as core materials, have been extensively investigated and used in various applications. One of the major limitations of the conventional materials used is their weak impact resistance and their end-of-life recyclability and overall sustainability. This paper is focused on the study of the production and mechanical characterization of hybrid sandwich panels using hemp bi-grid cores that were manufactured with an ad hoc continuous manufa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Shear testing evaluates the composites resistance to forces applied parallel to its surface. This is important for applications where the material may experience shear loads, such as implants subjected to torsional or shear forces [40]. The results of the characterization were to be used as input for material model during simulations using ANSYS.…”
Section: Materials Characterizationmentioning
confidence: 99%
“…Shear testing evaluates the composites resistance to forces applied parallel to its surface. This is important for applications where the material may experience shear loads, such as implants subjected to torsional or shear forces [40]. The results of the characterization were to be used as input for material model during simulations using ANSYS.…”
Section: Materials Characterizationmentioning
confidence: 99%
“…Placing hemp layers higher in the laminate (closer to the impact surface) resulted in a larger damage area but greater energy absorption for the hemp layers, reducing the propagation of internal damage through the laminate by 40% for the 10 J impact, thus showing that tailoring carbon/hemp composites could control composite failure modes and reduce damage propagation. Boccarusso et al [200] further analyzed carbon/hemp hybrids for structural applications by optimizing sandwich panels using hemp grids as the core for damage propagation, and they found that using a low-density Carbon and hemp hybrid composites were also considered for marine applications. One of the useful functions of CF/NF hybridization is combining the impressive strength and stiffness properties of CF with the interesting damping and impact energy absorption mechanism that limits damage propagation [199].…”
Section: Hybridization Strategies (Synthetic/natural Reinforcement)mentioning
confidence: 99%
“…Placing hemp layers higher in the laminate (closer to the impact surface) resulted in a larger damage area but greater energy absorption for the hemp layers, reducing the propagation of internal damage through the laminate by 40% for the 10 J impact, thus showing that tailoring carbon/hemp composites could control composite failure modes and reduce damage propagation. Boccarusso et al [200] further analyzed carbon/hemp hybrids for structural applications by optimizing sandwich panels using hemp grids as the core for damage propagation, and they found that using a low-density hemp grid for the core resulted in relatively ductile behavior with large deformations compared to the high-density core (double the number of hemp tows per unit area), which resulted in a stiffer, more brittle response. LVI tests also showed the low-density core samples to be more efficient at dissipating impact energy, as illustrated in Figure 10, which shows energy absorbed per energy level for low-density and high-density samples.…”
Section: Hybridization Strategies (Synthetic/natural Reinforcement)mentioning
confidence: 99%
“…An experimental and numerical study was conducted by Njim et al [57] to study the flexural properties of sandwich beams reinforced with nanoparticles (Al/Al 2 O 3 ). Furthermore, further studies have been conducted on composite structure design, testing, and evaluation [58][59][60].…”
Section: Introductionmentioning
confidence: 99%